Ethical conflicts detected by psychologists of Primary Health Care - Pérez Ayala, Manuel (Acta Bioethica, 2019)
Objectives: To identify the detection of ethical conflicts by psychologists in the context of PHC, determine their understanding and analyze the description of each one. Design: Qualitative study, exploratory-descriptive type. Participants: 25 psychologists, from a total universe of 28 professionals. Method: The data collection instrument was the semi-structured interview and the results analysis technique was the narrative analysis of content. Results: The informants detected a total of thirty-eight clearly differentiated ethical conflicts, arguing fourteen of them as critics. The categorization allowed differentiating three different categories from where they are established and represent: a) attention to consultants; b) relationship between colleagues and with other health professionals; and c) work context in public health. Conclusions The study allowed access to the problems perceived by the informants, agreeing that several of these conflicts have remained naturalized and normalized over time. The need arises to review and make visible the identified questions in order to establish the minimums necessary to be guarantors of quality interventions and excellence required in the mental health of the primary level of care.